Pengaruh model pembelajaran inkuiri terbimbing terhadap kemampuan berpikir kritis matematis siswa pada fase E SMK negeri 3 Pekanbaru - Puspita, Iwa; Indriati, Mefa; Wahyuni, Astri; Anggraini, Lilis Marina (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2024)
The objective of this study is to assess the effect of guided inquiry learning polas on the mathematical critical thinking abilities of students in phase E at SMK Negeri 3 Pekanbaru. The research employs a Bukanequivalent Control Group Design, focusing on the population of phase E students at the institution. A random sampling method was utilized to select two classes, with class X BP 1 designated as the experimental group and class X BP 2 as the control group. The assessment tools consisted of sebelum tes and sesudah tes essay questions designed to measure critical thinking skills. Hypothesis testing was conducted using a bukan-parametric data analysis technique for comparing two averages, specifically the Mann-Whitney U test. The results of the hypothesis test indicated a significance value of Asymp.Sig (2-tailed) at 0.014, which is less than the threshold of 0.05 (0.014 < 0.05). Consequently, the null hypothesis (H0) is rejected, and the alternative hypothesis (H1) is accepted, leading to the conclusion that guided inquiry learning polas significantly influence students' mathematical critical thinking skills.